2016
DOI: 10.3928/00904481-20160323-01
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in Children: A Practical Review

Abstract: Pediatricians and other child care providers manage a large number of children with constipation, a recurrent medical problem that is frustrating to patients, their care givers, and the health care providers themselves. Most often the constipation in children is functional in nature, and only a very small percentage of patients have an organic cause for it. In this review, we discuss the epidemiology, causes, evaluation, and management of children with functional constipation. [Pediatr Ann. 2016;45(5):e189-e19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Functional constipation in children is defi ned as constipation that occurs without an organic cause. [7][8][9] The Rome IV guidelines establish diagnostic criteria based on age. 9 Diagnosis of most children who have an organic cause will be done in the neonatal period.…”
Section: Constipationmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional constipation in children is defi ned as constipation that occurs without an organic cause. [7][8][9] The Rome IV guidelines establish diagnostic criteria based on age. 9 Diagnosis of most children who have an organic cause will be done in the neonatal period.…”
Section: Constipationmentioning
confidence: 99%
“…9 Diagnosis of most children who have an organic cause will be done in the neonatal period. 7 Constipation accounts for 3% of pediatric visits, and 25% of all pediatric gastroenterologist visits. 7,8 Complications from constipation include stool impaction and encopresis.…”
Section: Constipationmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with CIC always suffer from abdominal pain, painful bowel movements, large stools, and fecal incontinence (2,3). At present, the standard medical care of functional constipation contains dietary adjustment, toilet training, reassurance, education, and the use of laxatives (2,4,5). It was reported that 50% of the children receiving standard medical care (SMC) still have symptoms after several years and that the complaints might persist till adulthood (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, intestinal habitus is a personal characteristic varying considerably among individuals due to factors such as quality and quantity of ingested food and drink, convenience and a satisfied feeling of well-being, with no discomfort and without the sensation that evacuation was not sufficient [2].…”
Section: Introductionmentioning
confidence: 99%